PENGARUH KONFLIK KERJA DAN JAMINAN SOSIAL TERHADAP TURNOVER INTENTION MELALUI KEPUASAN KERJA KARYAWAN BAGIAN PRODUKSI PT. RIAU CRUMB RUBBER FACTORY KOTA PEKANBARU - Randi Saputra; Dewita Suryati Ningsih; Rovanita Rama (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This research was conducted at PT. Riau Crumb Rubber Factory Of Pekanbaru for the purpose of analyzing the effect of Work Conflict and Social Security on Turnover Intention through Employee Job Satisfaction Productioning Section. The population in this research is numbered 116 employees using the census method obtained the number of samples is equal to the total population of 116 people. Engineering data is done through techniques collection questionnaires, interviews, while the data in the form of primary data and secondary data, then the data were analyzed using path analysis of the data. The coefficient of determination, correlation coefficients and partial test. In this research, there are four variables: Job Satisfaction (Y1) and Turnover Intention (Y2), as the dependent variable and independent variables consist of Work Conflict (X1) and Social Security (X2). This research was conducted by giving questionnaires to employees of the productioning PT. Riau Crumb Rubber Factory Of Pekanbaru.Keywords : Work Conflict,Social Security,Job SatisfactionandTurnover Intention